The Tell-tale Patterns of Fantasy and History in Dastan Narratives: A Dialectical Perspective in Hoshruba - Nadeem, Farrukh; Javed Iqbal, Usama (Journal of Research in Humanities, 2023)
Despite the absurdly demonstrated actions and events of Dastan narratives, there is a dialectical relationship between reality and imagination or between history and fantasy. The ongoing conflict between the enigmatic and mythical characters of Hoshruba and the historically real figures creates a compelling narrative in Dastan. This epic story depicts the adventures of Amir Hamza and his commanders across various locations of Indo-Islamic civilization. Amir Hamza and his allies wage war against the entirely fictional characters of Hoshruba, a realm filled with powerful magic and mesmerizing enchantments. As a result, the dynamic relationship between these opposing forces leads to a series of exciting actions and events. Amid the brutal battles, there is also a captivating love story between the brave heroes of Amir Hamza’s camp and the alluring princesses of Hoshruba. These romances are fostered through seduction, cunning tricks, and clever traps. The research aims to examine how the interplay of imagination contributes to the Hoshruba narrative discourse and influences the course of events in the overall structure of Dastan, Hoshruba, the Land, and Tilism